Recycling of endocytic BDNF through extracellular vesicles in astrocytes - Jeongho Han; Hyungju Park (Scientific Reports)
Abstract Brain-derived neurotrophic factor (BDNF) plays an essential role in regulating diverse neuronal functions in an activity-dependent manner. Although BDNF is synthesized primarily in neurons, astrocytes can also supply BDNF through various routes, including the recycling of neuron-derived BDNF. Despite accumulating evidence for astrocytic BDNF uptake and resecretion of neuronal BDNF, the detailed mechanisms underlying astrocytic BDNF recycling remain unclear. Here, we report that astrocytic resecretion of endocytosed BDNF is mediated by an extracellular vesicle (EV)-dependent secretory pathway. In cultured primary astrocytes, extracellular BDNF was endocytosed into CD63-positive EVs, and stimulation of astrocytes with ATP could evoke the release of endocytosed BDNF from CD63-positive vesicles. Downregulation of vesicle-associated membrane protein 3 (Vamp3) led to an increase in the colocalization of endosomal BDNF and CD63 but a decrease in extracellular vesicle release, suggesting the necessity of Vamp3-dependent signaling for EV-mediated BDNF secretion. Collectively, our findings demonstrate that astrocytic recycling of neuronal BDNF is dependent on the EV-mediated secretory pathway via Vamp3-associated signaling.